Plan de negocios para la creación de una empresa de servicios de cicloturismo en la región Sierra del Ecuador - Peñaherrera Caicedo, Edison Sebastián (2018)
The idea of this business plan is to implement a bicycle tour services company, for domestic and foreign tourists. The use of the geography of Ecuador will provide special support to carry out this project. The impetus that the Ecuadorian government has given to the tourist industry is another important factor for the creation of this business plan idea. According to the information obtained from focus groups, interviews with experts on topics related to adventure tourism, the tourism industry and cycling sports, helped to gather important information that helped the implementation of the business plan. In this way, it is known that sports tourism is a growing trend, today many people prefer to practice this type of tourism. In the surveys carried out on 52 people who practice sports, 90 percent would be willing to cycle through theSierra del Ecuador region, with varied routes and diverse landscapes. The most important thing to keep in mind is the safety of the participants. The NPV of the project is 179,27.24 dollars, which denotes the viability of the business plan and a TIR of 35 percent.